1996
DOI: 10.1083/jcb.134.5.1313
|View full text |Cite
|
Sign up to set email alerts
|

Integrin-associated protein immunoglobulin domain is necessary for efficient vitronectin bead binding.

Abstract: Abstract. Integrin-associated protein (IAP/CD47) is physically associated with the e~v133 vitronectin (Vn) receptor and a functionally and immunologically related integrin on neutrophils (PMN) and monocytes. Anti-IAP antibodies inhibit multiple phagocyte functions, including Arg-Gly-Asp (RGD)-initiated activation of phagocytosis, chemotaxis, and respiratory burst; PMN adhesion to entactin; and PMN transendothelial and transepithelial migration at a step subsequent to tight intercellular adhesion. Anti-lAP anti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
111
0
1

Year Published

1997
1997
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 120 publications
(117 citation statements)
references
References 40 publications
5
111
0
1
Order By: Relevance
“…With a few exceptions (4), the CD47 antibody B6H12 has been generally found to block responses mediated by other CD47 ligands (7,17,(31)(32)(33)(34)(35). Our data confirm that B6H12 reverses the activation of ␣ v ␤ 3 integrin function stimulated by a CD47-binding peptide from TSP1, but we also show that the antibody has a direct stimulating function for at least two ␤ 1 integrins in the same cells.…”
Section: A Cd47-binding Peptide Stimulatessupporting
confidence: 77%
See 1 more Smart Citation
“…With a few exceptions (4), the CD47 antibody B6H12 has been generally found to block responses mediated by other CD47 ligands (7,17,(31)(32)(33)(34)(35). Our data confirm that B6H12 reverses the activation of ␣ v ␤ 3 integrin function stimulated by a CD47-binding peptide from TSP1, but we also show that the antibody has a direct stimulating function for at least two ␤ 1 integrins in the same cells.…”
Section: A Cd47-binding Peptide Stimulatessupporting
confidence: 77%
“…Involvement of different integrins in the opposing responses to B6H12 on vitronectin and NoC2 was confirmed using a specific ␣ v integrin antagonist, which reversed FIRVVMYEGKK-enhanced spreading on vitronectin but not on NoC2 (results not shown). B6H12 was previously considered to be a function-blocking antibody for CD47 (7,17,(31)(32)(33)(34)(35), but the above results demonstrate that this CD47 antibody can both positively and negatively modulate integrin functions. Furthermore, enhancement of some TSP1 peptide responses by the antibody indicated that B6H12 does not directly inhibit binding to their cellular targets.…”
Section: A Cd47-binding Peptide Stimulatesmentioning
confidence: 83%
“…The stable transfections of ␣ v ␤ 3 , CD47, and IgV-GPI have been previously reported by Lindberg et al (13), and the cells used in this study were derived from the same lines. For all experiments, OV10 cells were previously treated with serum-free media for 16 -18 h. Cell manipulations were carried out in Hanks Balanced Salt Solution containing 20 mM HEPES pH 7.5 (HBSS) with additional reagents for each application.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, 4N1K peptide-induced activation of ␣ IIb ␤ 3 , as measured by binding of PAC-1 antibody to transfected cells, required only the presence of the extracellular IgV domain of CD47, added either as a soluble protein or expressed with a generic membrane anchor (12). In addition, a previous study had shown that expression of the CD47 extracellular IgV domain in ovarian carcinoma cells was required for ␣ v ␤ 3 -mediated binding of vitronectin-coated beads (13). These data indicate that the physical association of only the IgV domain of CD47 can affect ␤ 3 integrin function.…”
mentioning
confidence: 99%
“…The wild-type and mutant SHPS-1 cDNAs were inserted separately into the EcoRI and NotI sites of the pTracerCMV vector (Invitrogen). The full-length mouse CD47 cDNA was excised from pIAP328 (32) and subcloned into pTracerCMV. The pRc/CMV vector encoding hemagglutinin (HA) 1 epitope-tagged mouse focal adhesion kinase (FAK) was provided by S. Hanks (Vanderbilt University).…”
Section: Methodsmentioning
confidence: 99%